A new accident analysis and investigation model for the complex building fire using numerical reconstruction. (September 2019) - Zhang, Guowei; Zhou, Xiang; Zhu, Guoqing; Yan, Su
Abstract: Fire accident investigation has always been difficult, because of complexities of fire occurrence and development and the non-repeatability of similar fire accidents. In this study, a fire investigation method is proposed based on the computer-aided fire scene reconstruction technique, realizing an effective combination of the fire accident investigation and computer simulation. Based on the investigation of traditional accident material evidence, this method uses the fire scene reconstruction technique to reconstruct fire occurrence and its development and catastrophe process through simulation. Then, this technique was successfully used to investigate a case study on a fire taking place in a multi-story residential building with personal casualties. From fire investigate, we can see that this method can offer assistance in identifying the cause of fire, assessing the losses caused by it, ascertaining where the responsibility lies, according to law, and presenting some significance for guiding the prevention of fire accidents in complex geometrical space.